JEJAK WUJUD ARSITEKTURAL DAN RAGAM HIAS CANDI KURUNG STUDI KASUS: PURA ULUWATU DAN PURA SAKENAN - Nyoman Ratih Prajnyani Salain; Ni Made Mitha Mahastuti (Jurnal Arsitektur ZONASI, 2022)
This study will discuss the architectural forms and decorations used in the case studies at Uluwatu Temple and Sakenan Temple. The two temples were chosen to be the object of research because they have similar architectural forms and styles although they are not the same as a whole. There are three issues raised, namely analyzing the similarity of shape, form and decoration at Kurung Temple at Uluwatu Temple and Sakenan Temple; the historical connection between the two Kurung Temples; strategies and conservation activities that need to be carried out at Uluwatu Temple and Sakenan Temple.The method used in this research is descriptive qualitative method, with triangulation data collection techniques that combine direct observation, survey and interview techniques. The hope of this research is that the academic community and the general public understand the correlation between architectural forms and decorations in the two Kurung Temples along with their historical values.Keywords:  Architectural Form, Decorative Variety, Kurung Temple, Uluwatu Temple, Sakenan Temple